2014
DOI: 10.3899/jrheum.130803
|View full text |Cite
|
Sign up to set email alerts
|

Blood Monocyte Heterogeneity and Markers of Endothelial Activation in Ankylosing Spondylitis

Abstract: Our findings suggest a contribution of immune dysregulation to enhanced monocyte-endothelial interactions in AS, especially in patients with active disease, which possibly can accelerate atherogenesis on a longterm basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 50 publications
3
24
1
1
Order By: Relevance
“…We found a positive correlation between serum sICAM-1 and IL-6 and ESR in SpA. Some studies have shown high sICAM-1 levels in the serum of patients with AS [2,31]. Wendling et al [34] found a positive correlation between sICAM-1 and ESR, CRP, and IL-6 in SpA patients.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We found a positive correlation between serum sICAM-1 and IL-6 and ESR in SpA. Some studies have shown high sICAM-1 levels in the serum of patients with AS [2,31]. Wendling et al [34] found a positive correlation between sICAM-1 and ESR, CRP, and IL-6 in SpA patients.…”
Section: Discussionsupporting
confidence: 64%
“…These authors found that after treatment, tissue IL-18 expression was changed, and they concluded that IL-18 plays a role in the pathophysiology of inflammatory arthritis [28]. On the other hand, Surdacki et al [31], in a group of AS patients smaller than that in our study, found no differences in serum IL-18 levels between AS patients and controls. We found no differences in serum IL-18 levels between the AS, PsA, and SAPHO groups.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Indeed, CSF3R (granulocyte colonystimulating factor receptor) is important for neutrophil production; however, it is also essential for the mobilization of CSF3R-expressing classic (CD162) monocytes (34,35). Previous studies in AS have shown an expansion of CD162 monocytes in the blood of patients with AS, with male patients tending to have higher levels of total monocytes compared with female patients (36). This suggests that the increase in myeloid genes we observed in the current study may be attributable to increases in the number of circulating classic CD162 monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…АС относится к факторам риска тяжелой сосуди-стой патологии [3,10], а вследствие васкулита мелких сосудов нарушается кровообращение сердца и голов-ного мозга, причем такие кардио-и цереброваскуляр-ные изменения коррелируют с продолжительностью патологического процесса [14], а также с тяжестью изменений опорно-двигательного аппарата [6]. Для АС характерно развитие аортита (иногда с формирова-нием аневризм [13]), что требует проведения диффе-ренциальной диагностики с аортоартериитом Такаясу и другими системными крупнососудистыми васкули-тами [4,9].…”
Section: Introductionunclassified